'DR Kinema': The Cinema, The Trade and the Rehabilitation of Wounded and Disabled Soldiers During the First World War. Issue 1 (2nd January 2020) - Grosvenor, Chris
Abstract : During the First World War, thousands of wounded and/or disabled soldiers were sent to hospitals and convalescent institutions across Britain to recover from both physical and psychological traumas endured whilst serving on the front. This article examines the role of the cinema within the context of soldier recovery and rehabilitation during the First World War, examining the practice of free/charity screenings for the returning wounded held in commercial cinemas, as well as the presence of non-theatrical exhibition in convalescent camps and hospitals. Drawing upon a wealth of contemporary historical evidence, this article outlines the many ways in which the medium intersected with the lives of those who returned from the front lines, demonstrating the cinema's ability to offer escapism and comfort for those in attendance. Attention is drawn towards the perspectives of both the military and medical authorities which implemented the cinema as a form of entertainment for wounded men, as well as the first-hand experiences of the soldier spectators themselves. By analysing these views and experiences, this article highlights the ways in which the cinema was utilised beyond the commercial interests of conventional theatrical venues for the benefit of the British war effort during the nation's time of crisis.